Harnessing natural terpenes via PEGylated mucoadhesive vesicles for improved urinary bladder delivery: from in vitro evaluation to in vivo assessment - Hammoodi, Hayder A.; Albash, Rofida; Hamed, Mohammed I. A.; Darwish, Khaled M.; Kassem, Amira B.; Saleh, Asmaa; Alamoudi, Jawaher Abdullah; Badawi, Noha M. (Frontiers in Pharmacology, 2025)
BackgroundFenticonazole nitrate (FTN)-loaded chitosan-coated PEGylated terpesomes (TPs) were investigated as a mucoadhesive formulation to enhance drug delivery to the urinary bladder.MethodsThe design of fenticonazole nitrate-loaded terpesome (FTN-TP) formulations was carried out using a 31.21 factorial design. The vesicles were evaluated for entrapment efficiency (EE%), particle size (PS), polydispersity index (PDI), and zeta potential (ZP). The selected FTN-TPs were further mixed with Gelucire® 44/14 as a PEG source and coated with chitosan to obtain the optimized chitosan-coated PEGylated terpesomes (CCPTs), which were then subjected to additional characterization.ResultsThe optimized CCPTs exhibited increased entrapment efficiency and zeta potential values without a significant increase in particle size or polydispersity index. They also demonstrated good mucoadhesive properties and remained stable for up to 90 days. Confocal laser scanning microscopy confirmed the penetration of the fluorescently optimized CCPTs through the urinary bladder wall. In silico studies indicated good stability of FTN when combined with other components in the optimized CCPTs. Moreover, in vivo evaluation revealed a significantly greater antifungal effect in rats treated with the optimized CCPTs compared to those receiving the FTN suspension. Histopathological examination further confirmed the safety of the optimum formulation for urinary bladder administration.ConclusionThe optimum formulation could serve as an effective alternative carrier for urinary bladder delivery of fenticonazole nitrate, prolonging its residence time and thereby enhancing its therapeutic pharmacological effect.